Effects of zinc supplementation on milk production performance and growth status of Bactrian camels - Zhou, Xinrui; Jiang, Menglei; Amjad, Muhammad; Khosbileg,; Liu, Miaoyu; Wu, Zihui; Cheng, Jiarui; Tang, Jiabin; Xu, Linghua; Zhu, Xuedan; Yang, Liguo; Hua, Guohua (Frontiers in Veterinary Science, 2025)
IntroductionBactrian camels have diverse agricultural roles, yet their nutritional needs, particularly for trace minerals like zinc, are not well understood.MethodsThis study investigated zinc supplementation’s effects on milk production, hump morphology, and hair development in lactating camels, and its impact on growth and hair development in calves. Seventy-nine lactating camels and their calves were assigned to four groups: a control group without zinc and three treatment groups receiving differential zinc sulfate concentrations.ResultsResults indicated that zinc supplementation had no significant effect on milk yield or composition compared to the control. Furthermore, zinc did not improve the proportion of camels with tilted humps across groups. However, Dose 3 (2.00 g/camel/day) significantly stimulated hair growth compared to the control, whereas Dose 1 (1.00 g/camel/day) and Dose 2 (1.50 g/camel/day) showed no significant differences. In calves, zinc demonstrated more pronounced effects: both Dose 1 (0.50 g/camel/day) and Dose 2 (0.75 g/camel/day) doses markedly enhanced body weight gain and hair development compared to the control. Dose 3 did not benefit calves.DiscussionCollectively, in the present study, zinc at 2.00 g/camel/day improved hair growth in lactating camels without affecting milk production, while 0.50–0.75 g/camel/day enhances growth and hair development in calves, establishing a basis for zinc supplementation in camel husbandry.